2017
DOI: 10.1039/c7nr01403a
|View full text |Cite
|
Sign up to set email alerts
|

Employing shells to eliminate concentration quenching in photonic upconversion nanostructure

Abstract: It is generally accepted that a lanthanide ions based upconversion material follows an activator low doping strategy (normally <3 mol%), because of the restriction of the harmful concentration quenching effect. Here, we demonstrate that this limitation can be broken in nanostructures. Simply by using an inert shell coating strategy, the concentration quenching effect for the activator (Er) could be eliminated and highly efficient upconversion luminescence realized in the activator fully doped nanostructure, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(82 citation statements)
references
References 45 publications
2
78
0
Order By: Relevance
“…In order to improve the luminescence intensity and detecting efficiency, researchers have proposed a variety of methods, such as ions co-doping, the introduction of transition metal ions, core-shell coating, plasmon resonance enhancement and so on. [21][22][23][24][25] Many studies have been reported on the introduction of smaller radius ions (Li + , Mn 2+ , Mg 2+ , etc.) [26][27][28] in UCNPs to enhance the upconversion emission, but few studies on the introduction of Zn 2+ ions into the rare-earth doped hexagonal phase NaYF 4 nanoparticles are presented.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the luminescence intensity and detecting efficiency, researchers have proposed a variety of methods, such as ions co-doping, the introduction of transition metal ions, core-shell coating, plasmon resonance enhancement and so on. [21][22][23][24][25] Many studies have been reported on the introduction of smaller radius ions (Li + , Mn 2+ , Mg 2+ , etc.) [26][27][28] in UCNPs to enhance the upconversion emission, but few studies on the introduction of Zn 2+ ions into the rare-earth doped hexagonal phase NaYF 4 nanoparticles are presented.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, this method can control the pumping of the specic level and regulate the luminescence color output. Zuo et al 18 reported that Er 3+ -doped sodium yttrium uoride (NaYF 4 ) samples were co-excited by three excitation sources such as 800 nm, 980 nm and 1530 nm. The UC emission intensities obtained from co-operative excitation are three times higher than the sum of UC intensities obtained using single laser excitation, which indicated that the UC properties of luminescence materials can be adjusted by multi-band coexcitation.…”
Section: -3mentioning
confidence: 99%
“…As shown in Figure 3c, the UC luminescence of this part is significantly increased when the NaYF4 shell gets thicker, until ~ 4.5 nm, which is in line with our previous report. 25 Besides, thicker S1 layer blocks better the energy transfer between the luminescent core (NaErF4) and S2 layer (NaYbF4: 0.5% Tm), in favour of strong UC luminescence. As shown in Figure S3, if S1 layer is not thick enough, say less than ~ 4.5 nm in our case, the components of the two parts will be diffused to a certain extent to the S1 layer which is unavoidable during the high temperature synthesis, and the diffused ions may interact with each other in the S1 layer which shall significantly reduce the UC emission of S2 layer (the UC emission of Tm 3+ can be well quenched by the diffused Er 3+ ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with conventional sensitizer/activator co-doping systems, this type of upconversion material system possesses very interesting UC luminescence properties, e.g. prominent quasi-monochromatic red upconversion emission of Er 3+ and much weaker emission in UV-Visible region, [23][24][25] owing to the ladder-like energy levels of Er 3+ , the robust Er 3+ -Er 3+ cross relaxation and the suppression of concentration quenching effect by shell protection, which shed light on developing high quality and less complex photoswitchable upconversion nanostructures.…”
mentioning
confidence: 99%